Efficacy of BRAF Inhibitors in Combination With Stereotactic Radiosurgery for the Treatment of Melanoma Brain Metastases: A Systematic Review and Meta-Analysis - Khan, Muhammad; Zheng, Tao; Zhao, Zhihong; Arooj, Sumbal; Liao, Guixiang (Frontiers in Oncology, 2021)
Abstract Background BRAF inhibitors have improved the outcome for patients with BRAF mutant metastatic melanoma and have shown intracranial responses in melanoma brain metastases. Stereotactic radiosurgery (SRS) is being used as a local treatment for melanoma brain metastasis (MBM) with better local control and survival. We searched for studies comparing the combination of two treatments with SRS alone to detect any clinical evidence of synergism. Methods & Materials PubMed, EMBASE, Medline, and Cochrane library were searched until May 2020 for studies with desired comparative outcomes. Outcomes of interest that were obtained for meta-analysis included survival as the primary, and local control as the secondary outcome. Results A total of eight studies involving 976 patients with MBM were selected. Survival was significantly improved for patients receiving BRAF inhibitor plus SRS in comparison to SRS alone as assessed from the time of SRS induction (SRS survival: hazard ratio [HR] 0.67 [0.58-0.79], p <0.00001), from the time of brain metastasis diagnosis (BM survival: HR 0.65 [0.54, 0.78], p <0.00001), or from the time of primary diagnosis (PD survival: HR 0.74 [0.57, 0.95], p=0.02). Dual therapy was also associated with improved local control, indicating an additive effect of the two treatments (HR 0.53 [0.31, 0.93], p=0.03). Intracranial hemorrhage was higher in patients receiving BRAF inhibitors plus SRS than in those receiving SRS alone (OR 3.16 [1.43, 6.96], p=0.004). Conclusions BRAF inhibitors in conjunction with SRS as local treatment appear to be efficacious. Local brain control and survival improved in patients with MBM receiving dual therapy. Safety assessment would need to be elucidated further as the incidence of intracranial hemorrhage was increased.